CCAT1 expressed in malignant and pre-malignant human gastric tissues - Li, X.; Zhou, Y.; Qian, H. (Cellular and Molecular Biology, 2017)
CCAT1 has been reported to implicate in various human malignancies. However, its expression in the oncogenesis of gastric cancer (GC) remains unknown. Quantitative reverse transcription (RT)-qPCR assay was performed to detect the expression of CCAT1 in 68cases of GC tissues,paired tumor-proximal gastric mucosa and normal gastric mucosa, 19 cases of gastric intraepithelial neoplasia (GIN), and the sera of these 68 GC patients and 22 healthy volunteers. And the relationship between CCAT1 and clinicopathologic features of GC patients were analyzed. Inthe present study, we found that CCAT1 expression was significantly abnormally deregulated in GC tissues (185.43 ± 21.37), GIN tissues (121.30 ± 43.61), tumor-proximal mucosa (8.9 ± 1.21), and normal mucosa (1.5 ± 0.55). CCAT1 wasalso overexpressed in the sera of GC patients (47.40 ± 6.60) compared with healthy controls (0.62 ± 0.06; p < 0.001). And high CCAT1 expression in GC tissues was associated with high tumor burden, including larger tumor size, lymphatic metastasis and advanced TNM stage (all p < 0.05). These results reveal that CCAT1 is a detectable biomarkerforgastric cancertumorigenesis and may be utilized as adiagnosticand prognosticindicator.